Students’ mathematical reasoning skills on number pattern using PMRI and collaborative learning approach - Siti Nabila; Ratu Ilma Indra Putri (Universitas Hamzanwadi, 2022)
Students need to have good mathematical reasoning skills when learning number pattern material. The use of video media through the PMRI approach and collaborative learning can be applied in learning activities to have good mathematical reasoning skills. This study aims to determine mathematical reasoning skills after implementing the learning process using video media with the PMRI approach and collaborative learning on number pattern material for class VIII students. This research uses a descriptive type of research. The research subjects were students of class VIII.A, SMP Srijaya Negara Palembang, with 25 students (12 males and 13 females) out of a total of 39 students. Data collection techniques are observation, a written test consisting of two test questions, and interviews. The data analysis technique is descriptive. The results obtained from this study are the students' mathematical reasoning skills after the learning process using video media with the PMRI approach and collaborative learning on the number pattern material of grade VIII.A students of SMP Srijaya Negara Palembang are good, with an average value of 68.89. The indicator that appears the most is